Meaning of life and its association with perspective towards life and way of living: A qualitative study in palliative care professionals - Limluck, Soonthorn; Pothisiri, Wiraporn; Rungnirundorn, Teerayuth (Chulalongkorn Medical Journal, 2022)
Background: Having the meaning of life plays an essential part in human life. It is shown to affect one’s perspective towards life and way of living, and is positively correlated with physical and mental health status. However, the meaning of life in palliative care staff was not yet explored. Objectives: This study aimed to uncover the meaning of life among the palliative care professionals, and to determine factors contributing to the meanings. The associations between the meaning of life and their professions and the way of life were also studied. Methods: Qualitative descriptive method was employed. Twelve palliative care professionals in the Palliative Care Unit were interviewed face-to-face using a semi-structured interview guide. Data were collected and analyzed by step-by-step thematic analysis. Results: Five themes emerged as the meaning of life in palliative care professionals which are: 1) transcendence; 2) love and attachment; 3) duty and contribution to the world; 4) appreciation of beauty and joy in life; and, 5) purposes in life. The key factors contributing to the meaning are the palliative professions and individual factors. The meaning of life is greatly contributed to each subject’s perspective towards life and the way of living. Conclusion: Working in palliative profession has greatly impacted the perception of life as an uncertain matter and the meaning of life which affect the ways of living. These findings suggest the promotion of having the meaning of life in other healthcare professions to enhance the quality of life of health professionals and to the society.